CTF vs FD Based Numerical Methods: Accuracy, Stability and Computational Time's Comparison. (November 2015) - Mazzarella, Livio; Pasini, Martina
Abstract: Conduction Transfer Function (CTF) and Finite Difference (FD) based numerical methods, are widely used to calculate transient heat conduction in Building Performance Simulation tools (BPSts). The first method is still preferred, when linear system are modelled, to the second one, thanks to the small computational time required during the simulation. However, current BPSts have not yet implemented effective warning messages to stop their "costumers" when these methods are misused. In this article, those methods are compared in terms of computational time and accuracy, with the aim of identifying selection criteria based on the specific addressed problem.